Migrastatics: Redirecting R&D in Solid Cancer Towards Metastasis? - Rosel, Daniel; Fernandes, Michael; Sanz-Moreno, Victoria; Brábek, Jan (Trends in cancer, 2019)
The concept of 'migrastatics' allows the development of a new drug class that is neither cytotoxic nor antiproliferative but is solely directed towards inhibition of cancer cell motility. Given that the regulatory pathway is open, and migrastatic candidates have been described, it is the right time to enter a new era of antimetastatic treatment.
Keywords: nádory; lidé; metastasis; invasiveness; invazivní růst nádoru; metastázy nádorů; Neoplasm Invasiveness; Neoplasms; migrastatic treatment; cancer therapy; Neoplasm Metastasis; Humans; Cell Line, Tumor; nádorové buněčné linie